Dystrophy of Oligodendrocytes and Adjacent Microglia in Prefrontal Gray Matter in Schizophrenia - Uranova, Natalya A.; Vikhreva, Olga V.; Rakhmanova, Valentina I.; Orlovskaya, Diana D. (Frontiers in Psychiatry, 2020)
Background. Some evidence support the notion that microglia activation in acute state of schizophrenia might contribute to damage of oligodendrocytes and myelinated fibers. Previously we found dystrophic changes of oligodendrocytes in prefrontal white matter in schizophrenia subjects displaying predominantly positive symptoms as compared to controls. The aim of the study was to verify whether microglial activation might contribute to dystrophic changes of oligodendrocytes in prefrontal gray matter in this clinical subgroup. Methods. Transmission electron microscopy and morphometry of microglia and adjacent oligodendrocytes were performed in layer V of the prefrontal cortex (BA10) in the schizophrenia subjects displaying predominantly positive symptoms (SPPS, n=12), predominantly negative symptoms (SPNS, n=9) and healthy controls (n=20). Results. Qualitative study showed microglial activation and dystrophic alterations of microglia and oligodendrocytes adjacent to each other in both subgroups as compared to controls. A significant reduction in volume density (Vv) and the number (N) of mitochondria and an increase in N of lipofuscin granules were found in oligodendrocytes and adjacent microglia in both subgroups. Vv of lipofuscin granules, Vv and N of vacuoles of endoplasmic reticulum in microglia were increased significantly in the SPPS subgroup as compared to controls. In the SPPS subgroup Vv and N of mitochondria in microglia were correlated with N of vacuoles in microglia (r=-0.61, p<0.05), Vv (r=0.79, p<0.01) and N (r=0.59, p<0.05) of mitochondria in oligodendrocytes. Vv of mitochondria in microglia was also correlated with Vv and N of vacuoles in oligodendrocytes (r=0.76, p<0.01). Area of nucleus of microglial cells was correlated negatively with age (r=-0.76, p<0.01) and age at illness onset (r=-0.65, p<0.05) in the SPPS subgroup. In the SPNS subgroup N of mitochondria in microglia was correlated with Vv of lipofuscin granules in oligodendrocytes (r=-0.89, p<0.01). There were no significant correlations between these parameters in the control group. Discussion: Microglial dystrophy might contribute to oligodendrocyte dystrophy in the schizophrenic subjects with predominantly positive symptoms during relapse. Mitochondria in microglia and oligodendrocytes may be a target for treatment strategy of schizophrenia.